TEORI KEADILAN DAN MORALITAS - Sufyan Assauri; Mahir Amin; Sri Warjiyati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study explores the evolution of legal theory and morality as the foundation for establishing justice within society. Legal theories encompass not only the formal aspects of positive law but also consider social dynamics and the relationship between law and morality. Historically, legal theory originated from theological beliefs, developed through natural law concepts, and culminated in legal positivism emphasizing concrete regulations. Meanwhile, morality is understood as a guide to Identifying what is right or bad in human behavior, and may be objective or subjective depending on its context. The concept of justice, as articulated by thinkers such as Aristotle and Rawls, spans various dimensions, including distributive, corrective, procedural justice, and fairness. Good law should reflect moral values, as sound morality fosters sound laws. Thus, the interplay between law and morality is crucial for achieving justice that is not only normative but also aligned with the dynamics of modern society